Reduce rework, improve safety: an empirical inquiry into the precursors to error in construction - Love, Peter; Teo, Pauline; Ackermann, Fran; Smith, J.; Alexander, James; Palaneeswaran, E.; Morrison, J. (Taylor & Francis, 2018)
A positive association between rework and safety events that arise during the construction process has been identified. In-depth semi-structured interviews with operational and project-related employees from an Australian construction organisation were undertaken to determine the precursors to rework and safety events. The analysis enabled the precursors of error to examined under the auspices of: (1) People, (2) Organisation, and (3) Project. It is revealed that the precursors to error for rework and safety incidents were similar. A conceptual framework to simultaneously reduce rework and safety incidents is proposed. It is acknowledged that there is no panacea that can be used to prevent rework from occurring, but from the findings presented indicate that a shift from a position of ‘preventing’ to ‘managing’ errors is required to enable learning to become an embedded feature of an organisation’s culture. As a consequence, this will contribute to productivity and performance improvements being realised.